Удмуртское модальное слово кулэ – имя прилагательное? - Koivunen, Tomi (A Debreceni Egyetemi Kiadó, 2026)
The Udmurt language has a modal word кулэ ’must; necessary’, which is historically a finite verb form. In modern language, the word occurs only in the fossilized third person singular form. Various sources consider the word to be a verb, an adverb, a ”modal word” or do not take a position on its classification. Кулэ usually occurs as a predicate, but it can also occur as an attribute, unlike finite verb forms in general. In addition, it can acquire the plural form of adjectives and nouns can be derived from it with stems that are usually associated with adjectives, e.g. кулэ + лык > кулэлык ’need’. The article discusses whether it would be more meaningful to classify the word as an adjective rather than a verb or adverb. Based on the corpus data, it seems that кулэ does not function in the same way as other Udmurt verbs, but it does not meet all the characteristics of adjectives either.